Does board gender diversity really improve firm performance? Evidence from Greek listed firms - Stavros E. Arvanitis; Evangelos G. Varouchas; George M. Agiomirgianakis (Journal of Risk and Financial Management, 2022)
In recent decades, the contribution of board gender diversity to corporate performance has drawn the interest of researchers, politicians and regulators. This paper examines whether board gender diversity affected the financial performance of 111 Greek listed firms from 2008 to 2020. We use the two-step system GMM estimator to address the endogeneity problem, which is the appropriate method used in governance literature. Our main empirical finding supports the existence of a positive relation between board gender diversity and firm performance. This finding remains robust to three different proxies of gender diversity and under two alternative performance measures, i.e., return on assets and Tobin's Q. We also find that there is an inverted U-shaped relation between the proportion of female directors and firm performance (measured by Tobin's Q). Moreover, we find that gender diversity could lead to maximization of corporate performance when female participation in the boardroom reaches 33%. Thus, the imposition of an ad-hoc 25% female representation in corporate boardrooms, dictated by the new Law 4706/2020 on corporate governance, could most probably be an underproductive policy. Our findings have practical implications for Greek regulators and legislators and contribute to the governance literature for the case of companies that operate in a small open economy.
Keywords: 650; corporate governance; board gender diversity; firm performance; Greece